Avaliação dos serviços de atendimento ao traumatizado de face no estado de Sergipe - Bomfim, Ana Marlusia Alves (2006)
Today the Brazilian cities have been the site of violent acts as consequence of the raise in the criminality, car accidents, violent sport activities, fall and interpersonal aggressions. Under the dentistry perspective, one should give attention to the face because it has been the target of constant traumas and lesions once it is the first contact in the interaction between the people. This work had the objective of diagnosing and analyzing the current state of the assistance to the face trauma victims in the state of Sergipe in what concerns the structure and the operation of the reference services (hospitals and ambulatories) of medium and high complexity. It was identified some relevant points about the assistance of victims of those traumas. The methodology used in this work was the descriptive explanatory study on seven pole-municipal districts in the health regions of the state of Sergipe. It was applied a questionary with 17 opened, closed and mixed questions. They were answered by the managers (coordinators and directors of the personnel of the hospitals and ambulatories staff) from each service of reference service. The data were submitted to the descriptive statistic analysis by means of distribution in percentage of the results. They pointed out that 65.1% of the units are precariously physically structured to assist somebody victim of trauma in the face. While 34.9% were satisfactorily prepared in structural terms to this activity. In what concerns the operation of those units, 61.6% presented failures on that category while 38.4% showed that they work satisfactorily. Those results had shown fragilities in the system of assistance system to the face trauma victim, once considering that they are units of reference. It allowed doing some suggestions to minimize the problem.